Wybrane uwarunkowania demograficzne korzystania z usług gastronomicznych (na przykładzie aglomeracji warszawskiej) - Kwiatkowska, Edyta (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2010)
In the last few years, a dynamic development of the service sector has been observed in Poland. An increase in the importance of services is a result of a civilisation development, and it is getting more and more meaningful due to an increasing number of employees and the value of provided services. The main aim of this study was to analyze the preferences of consumers from big cities (on the example of Warsaw) on choosing the place and the frequency of dining in restaurants. I have tried to find the relations between the chosen demographic indicators (age, sex, place of stay) and dining habits. It was noticed that dining in restaurants, for almost all taking part in the survey, is rather occasional than common. However, for some of the respondents, it is an everyday (or almost everyday) way of dining. It was also noticed that dining out is common for young people at the ages between 25 and 29.